The Impact of Carbon Tax Implementation in Indonesia on Supporting Sustainable Development Goals - Ababil, Ressy Yulia; Diana, Nur; Efendi, Erfan (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research aims to find out how the implementation of carbon tax in Indonesia can support the Sustainable Development Goals (SDGs). The author uses a descriptive qualitative approach, using secondary data. This research also uses documentation techniques in the information data collection process and uses data analysis methods with literature studies. The results show that the impact of carbon tax implementation in Indonesia can support Sustainable Development Goals by continuing to reduce greenhouse gas emissions in Indonesia. The above can support Sustainable Development Goals 13 (Climate Change). Keywords: Carbon tax, sustainable development goals